تجربة الوقف المؤقت: دراسة مقارنة بين دولة الكويت ودولة ماليزيا = Implementation of temporary Waqf: a comparative study between Kuwait and Malaysia - Ab Rahman, Muhamad Firdaus; Amanullah, Muhammad (Department of Fiqh and Usul, Academy of Islamic Studies, University of Malaya, 2017)
This research aims at comparing the implementation of temporary waqf between Kuwait and Malaysia by examining the articles in the Kuwait Waqf Law and waqf enactments in selected states in Malaysia namely; Selangor, Negeri Sembilan, Melaka and Johor. The research adopts a comparative method. The results illustrate that Section 19 of the Kuwait Waqf Law 1951 and Section 17 of Rules of Waqf Johor 1983 allow the application of temporary endowment for all types of waqf, the duration of temporary waqf should not exceed sixty years (60) and not more than two (2) generations. This paper proposes to encourage the other states in Malaysia and Islamic countries to implement temporary waqf as one of the waqf alternatives for the benefit of future generations.